Printing and Dyeing Physiognomies of Synthesized Azo-Multifunctional Reactive Dyes Using Exhaust Technique - Saeed, Q.; Bhatti, I.A.; Zuber, M.; Bhatti, H.N.; Zia, M.A. (Asian Journal of Chemistry, 2015)
Four poly-functional reactive dyes keeping mono or bis reactive group have been synthesized and applied successfully to cotton fabric. The main target of study was to synthesize novel reactive dyes having multiple reactive cites to show maximum colour strength. In order to explore the best dyeing conditions, dyeing parameters such as dyeing time, temperature and pH of dyeing bath as well as salt concentration were optimized. Textile printing is the most versatile method used for introducing varieties of design to textile fabrics. These synthesized dyes were applied to fabric for evaluating their printing potential. Fastness properties such as washing, light, rubbing, dry cleaning and perspiration were also investigated after application by exhaust method and printing techniques at Noor Fatima Textile Industry (Pvt.), Faisalabad, Pakistan. The percentage dye exhaustion and fixation was found to be reasonably good and acceptable. All the dyes, after fixation onto the fabrics, showed moderate to excellent fastness properties and colour strengths. The prints of these reactive dyes also demonstrated equitably good colour fixation and fastness characteristics.